Better by design: Business preferences for environmental regulatory reform - Taylor, Christopher M.; Pollard, Simon J. T.; Rocks, Sophie A.; Angus, Andrew (Elsevier, 2015)
We present the preferences for environmental regulatory reform expressed by 30 UK businesses and industry bodies from 5 sectors. While five strongly preferred voluntary regulation, seven expressed doubts about its effectiveness, and 18 expressed no general preference between instrument types. Voluntary approaches were valued for flexibility and lower burdens, but direct regulation offered stability and a level playing field. Respondents sought regulatory frameworks that: are coherent; balance clarity, prescription and flexibility; are enabled by positive regulatory relationships; administratively efficient; targeted according to risk magnitude and character; evidence-based and that deliver long-term market stability for regulatees. Anticipated differences in performance between types of instrument can be undermined by poor implementation. Results underline the need for policy makers and regulators to tailor an effective mix of instruments for a given sector, and to overcome analytical, institutional and political barriers to greater coherence, to better coordinate existing instruments and tackle new environmental challenges as they emerge.
Keywords: Environmental policy; Regulation; Regulatory reform; Instrument selection